Vertical transmission of porcine circovirus-like virus P1 in BALB/c mice - Shaoyang Sheng; Lin Guan; Jianping Xie; Qi Xiao; Libin Wen; Kongwang He (BMC Veterinary Research, 2023)
Abstract Background Porcine circovirus-like virus P1 is the animal virus with the smallest genome discovered so far, and it has become widely distributed in the Chinese mainland in recent years. Results In this study, a BALB/c mouse model was used to reveal P1 infection in female reproductive systems and the vertical transmission of the virus. The female reproductive system, including the ovary and uterus, was harvested on day 14 postinfection and examined for pathological lesions. One-day-old mice without colostrum born from infected or uninfected mothers were collected, and P1 virus distribution in the different organs was investigated. During the trials, all the mice showed no clinical symptoms or gross lesions. However, stillbirth did occur in groups infected with the P1 virus. P1 nucleic acid was detected in the heart, liver, spleen, lung, kidney, and brain tissues of 1-day-old mice born from infected mice. Microscopic lesions in P1-infected female mice were characterized by necrosis of the ovarian follicular granulosa cells and abscission, follicular atresia, necrosis of the endometrial epithelial and uterine glandular epithelial cells, and hyperplasia of the squamous endometrial epithelium. The spermatocytes in the seminiferous tubules of the infected male mice were disorderly arranged, and the germ and Sertoli cells were shed, necrotic, and decreased in number. Immunohistochemical results identified P1-positive particles in the nucleus and cytoplasm of cells from the ovary and uterus of female mice. Conclusions This study shows that the P1 virus could cause pathological damage to the reproductive system of female mice and could be transmitted vertically.